The "Sponge sign": A novel feature of inflammatory choroidal neovascularization. Issue 3 (May 2021) - Giuffrè, Chiara; Marchese, Alessandro; Fogliato, Giovanni; Miserocchi, Elisabetta; Modorati, Giulio Maria; Sacconi, Riccardo; Cicinelli, Maria Vittoria; Miere, Alexandra; Amoroso, Francesca; Capuano, Vittorio; Souied, Eric; Bandello, Francesco; et al.
Introduction: To investigate choroidal thickness changes related to the clinical activity of inflammatory choroidal neovascularization in punctate inner choroidopathy/multifocal choroiditis as compared to myopic choroidal neovascularization. Materials and methods: Consecutive inflammatory choroidal neovascularization secondary to punctate inner choroidopathy/multifocal choroiditis, and myopic choroidal neovascularization were retrospectively reviewed. By means of enhanced-depth imaging optical coherence tomography, choroidal thickness was assessed at the same location before choroidal neovascularization development, at choroidal neovascularization onset (baseline), and after treatment. Results: Eleven eyes with inflammatory choroidal neovascularization and 11 eyes with myopic choroidal neovascularization were analyzed. Choroidal thickness beneath inflammatory choroidal neovascularization significantly increased at baseline and decreased after therapy ("Sponge sign"), reaching preclinical values. In particular, mean choroidal thickness under inflammatory choroidal neovascularization was 145 ± 85 µm at the preclinical stage, increased to 210 ± 103 µm at baseline (p = 0.006), and decreased to 136 ± 87 µm after treatment (p = 0.017). Conversely, no significant choroidal thickness changes were disclosed in myopic choroidal neovascularization eyes, under any location. Conclusion: Optical coherence tomography–based choroidal thickness evaluation may represent an additional useful tool to monitor inflammatory choroidal neovascularization activity. Moreover, choroidal thickness under choroidal neovascularizations could be used to discriminate the origin of choroidal neovascular membrane, either inflammatory or myopic, in doubtful cases and guide the therapeutic management.